Pengaruh Kualiitas Pelayanan, Kewajiban Moral, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Hotel dan Restoran di Kabupaten Badung - Ni Made Putri Delita Sari; I Gusti Ngurah Sanjaya; Luh Putu Lusi Satyandarini Surya (Jurnal Riset Akuntansi Warmadewa, 2021)
This research was conducted on hotels and restaurants in Badung Regency. The formulation of the problem in this investigation is to test whether the quality variables of service, moral moral variables, and variables of taxation penalty have an influence on the compliance of hotel and restaurant taxpayers in badung district. the data in this study was collected by disseminating questionnaires to hotel and restaurant taxpayers in Badung Regency using random sampling techniques in sampling, where the questionnaire was distributed as many as 98 kursioner. This study uses multiple linear regression analysis techniques that will be combined with the SPSS (Statistical Package for Social Science) computer program. This study showed the results that variable (X1) quality of service, variable (X2) moral obligation, and variable (X3) tax sanctions showed positif results.